COMPARATIVE EFFECT OF STATIC AND DYNAMIC STRETCHING EXERCISE TO IMPROVE FLEXIBILITY OF HAMSTRING MUSCLES AMONG NON ATHLETES - Jibi Paul; Pradeep Balakrishnan; Mohd Izham (International Journal of Physiotherapy, 2014)
Background: Stretching exercises have been routinely used in persons with hamstring tightness and athletes to increase flexibility of muscle and to reduce joint injuries. Many studies have reported effect of static and dynamic stretching on flexibility of this muscle. Finding the best method to improve flexibility of hamstring muscle is important for athletes and individuals to reduce their injuries. Objective of the study was to find out the effect of static stretching exercise and dynamic stretching exercise on flexibility of hamstring muscle and also to compare the effect of static and dynamic stretching exercise on flexibility of hamstring muscle. Methods: This was a comparative experimental study with seventy four female healthy subjects from physiotherapy department of KPJ Healthcare University College, Malaysia. Convenient sampling method used to select the samples. The subjects were selected by inclusion criteria and randomly divided equally in to two with 37 subjects in each group. Static stretching exercise and dynamic stretching exercise were given as intervention program for four weeks respectively for experimental and control group. Pre and post data of restricted range of movement for knee extension was measured using goniometry and documented separately for both group. Result: In experimental and control group, pre-post statistical analysis found significant effect in increase of hamstring flexibility with P<0.0001, for right and left side. Comparative study between experimental and control group found that static stretching exercise have significant effect in increase of hamstring flexibility for right and left side with P<0.04. Conclusion: This study concluded that static stretching exercise is more effective to improve hamstring flexibility compared to dynamic stretching exercise.